(untitled) (Scientific journal of the Fergana State University, 2024)
This article analyzes the institutional system of global environmental control and future tasks of improving international environmental political relations from substantive and functional aspects are discussed. Also the article indicates the effectiveness of international environmental control institutions depends on a differentiated approach to local, national and regional characteristics of the environmental situation, the use of optimal methods and tools.